2011
DOI: 10.1016/j.lfs.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Glycine intrastriatal administration induces lipid and protein oxidative damage and alters the enzymatic antioxidant defenses in rat brain

Abstract: The data shows that Gly in vivo administration causes lipid peroxidation, probably secondary to NMDA stimulation, induces protein oxidation and modulates the activities of important antioxidant enzymes in the striatum. In case these findings can be extrapolated to the human NKH, it is feasible that oxidative stress may be involved in the pathophysiology of the brain injury observed in patients with this neurometabolic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Considering that oxidative stress has been considered an important underlying pathomechanism of common neurodegenerative disorders (Berg and Youdim, 2006; Mancuso et al, 2006; Stoy et al, 2005) and of some inborn errors of metabolism (Busanello et al, 2011; Ribas et al, 2011; Seminotti et al, 2011), in the present work we investigated the effects of MCAC on a large spectrum of relevant parameters of redox homeostasis in cerebral cortex from young rats. We used cerebral cortex in this investigation because brain abnormalities are seen in this structure in MCAD deficient patients.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that oxidative stress has been considered an important underlying pathomechanism of common neurodegenerative disorders (Berg and Youdim, 2006; Mancuso et al, 2006; Stoy et al, 2005) and of some inborn errors of metabolism (Busanello et al, 2011; Ribas et al, 2011; Seminotti et al, 2011), in the present work we investigated the effects of MCAC on a large spectrum of relevant parameters of redox homeostasis in cerebral cortex from young rats. We used cerebral cortex in this investigation because brain abnormalities are seen in this structure in MCAD deficient patients.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of nonketotic hyperglycinemia is complex. In addition to end-product deficiency of 5,10-methylenetetrahydrofolate [7][8][9], glycine toxicity both directly [10][11][12][13][14] and through excess glycine simulation at the allosteric site of the NR1/NR2 NMDA receptor [15][16][17] is hypothesized to be a major factor.…”
Section: Introductionmentioning
confidence: 99%
“…In the experimental study, administration of glycine to animals in contrast to the expected renal cytoprotection was associated with an increase in acute ischemic-reperfusion renal injury as a result of NMDA activation (Arora et al 2014). It has been demonstrated that NMDA activation is associated with increased intracellular calcium, impairment of nitric oxide synthesis, and increased production of reactive oxygen species, and is the one of the key causes in pathogenesis of heart failure (Kang et al 2009;Seminotti et al 2011;Martins-Pinge et al 2013;Stern and Potapenko 2013;Moura et al 2014). The role of NMDA activation in the pathogenesis of ischemic/reperfusion injury has been confirmed by the cytoprotective effect of the NMDA inhibition, especially, in pre-and postconditioning of the isolated rat heart (Weinberg et al 2016;Govoruskina et al 2019).…”
Section: Discussionmentioning
confidence: 99%